A new rechargeable battery based on a zinc anode and a NaV6O15 nanorod cathode. Issue 26 (13th March 2019) - Islam, Saiful; Alfaruqi, Muhammad Hilmy; Sambandam, Balaji; Putro, Dimas Yunianto; Kim, Sungjin; Jo, Jeonggeun; Kim, Seokhun; Mathew, Vinod; Kim, Jaekook
Abstract : A NaV6 O15 nanorod cathode exhibits long-term cyclability with nearly 100% coulombic efficiency at 50/100 mA g −1 current density. Abstract : We explore NaV6 O15 (NVO) nanorod cathodes prepared by a sol–gel method for aqueous rechargeable zinc-ion battery applications for the first time. The NVO cathode delivers a high capacity of 427 mA h g −1 at 50 mA g −1 current density. Furthermore, based on the mass of the active materials, it exhibits a high energy density of 337 W h kg −1 .